2019
DOI: 10.1257/aeri.20180633
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Success in Education: The Role of Effort on the Test Itself

Abstract: US students often rank poorly on standardized tests that estimate and compare educational achievements. We investigate whether this might reflect not only differences in ability but also differences in effort on the test. We experimentally offer students incentives to put forth effort in two US high schools and four Shanghai high schools. US students improve performance substantially in response to incentives, while Shanghai students—who are top performers on assessments—do not. These results raise the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…Carroll, 1963), grit (e.g. Duckworth et al, 2007), intrinsic motivation, self-motivation, and other executive function skills (such as in Cunha et al, 2010;Gneezy et al, 2019;Kosse et al, 2020;Cappelen et al, 2020), to describe time preference, our metric is theoretically-driven, clearly defined, and quantifiable. Likewise, while aptitude, cognitive ability, and innate ability have been used to measure academic efficiency, we develop a theoretically-consistent metric that is easily obtained and correlates with key observables.…”
Section: Introductionmentioning
confidence: 99%
“…Carroll, 1963), grit (e.g. Duckworth et al, 2007), intrinsic motivation, self-motivation, and other executive function skills (such as in Cunha et al, 2010;Gneezy et al, 2019;Kosse et al, 2020;Cappelen et al, 2020), to describe time preference, our metric is theoretically-driven, clearly defined, and quantifiable. Likewise, while aptitude, cognitive ability, and innate ability have been used to measure academic efficiency, we develop a theoretically-consistent metric that is easily obtained and correlates with key observables.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning juvenile delinquents, there were observed problems (e.g., the SDQ), but self-esteem might not be the panacea claimed. Many programs call for extreme praise, such as at the rate of praise to reprimand as high 9:1 (Caldarella et al, 2019), yet many studies suggested praise was either not effective or might be harmful (Brummelman et al, 2017;Lepper et al, 1973;Gneezy et al, 2019;Moore et al, 2019). Other efforts included eliminating grade retention because it was harmful to students (Hughes et al, 2018;Klapproth et al, 2016) and the negative effects of school exclusionary policies in favor of letting students escape meaningful discipline (Anyon et al, 2014;Eyllon et al, 2020) Yet, mantras around grit, self-esteem, growth mindset, and other constructs did not transform students and instill academic and social skills with emotional stability.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no differences between no pay and very low pay, but did detect increases in submission rates and grades for the higher incentive levels. Gneezy et al (2019) vary monetary incentives on an international standardized exam from roughly $30 to $90 and report that American students improve scores from incentives, but Chinese students did not, suggesting that the effects of incentives are sensitive even to cultural differences.…”
Section: Negative Evidence On Crowding Outmentioning
confidence: 99%